Haemato-biochemical changes in propofol with 2% Lignocaine Continuous Rate Infusion (CRI) in dogs - Kumar, Mithilesh; Prabhakar, Vishnu; Sinha, Ranveer Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present research work was conducted to study the effect of propofol on haemato-biochemical and physiological parameters. A total of twelve adult dogs divided into six (6) animals in each group viz Group-I (Maintenance by propofol) and Group-II (maintenance by propofol and 2% lignocaine CRI) were presented for removal of infected uterus. Haematological parameters and biochemical parameters were within their normal physiological range in all groups. Based on the clinical, biochemical, hematological parameters propofol-lignocaine combination was more suitable.